Correlation between bony structures of the posterior cranial fossa and the occurrence of hemifacial spasm - Tang, Tianjin; Yang, Wenqiang; Wang, Qi; Yu, Yanbing; Zhang, Li (Frontiers in Neurology, 2024)
Objective To quantitatively study the measurement data related to the bony posterior cranial fossa and explore the correlation between bony posterior cranial fossa morphology and the occurrence of hemifacial spasm. Methods A total of 50 patients with hemifacial spasm who attended the Department of Neurosurgery of China-Japan Friendship Hospital from October 2021 to February 2022 were included, and 60 patients with minor head trauma excluding skull fracture and intracranial abnormalities were included as controls. Cranial multilayer spiral CTs (MSCTs) were performed in both groups, and multiplanar reconstruction (MPR) was used as a postprocessing method to measure data related to the posterior cranial fossa in both groups. Results Compared with the control group, the anteroposterior diameter (labeled AB) and the height (labeled BE) of the bony posterior cranial fossa, the anteroposterior diameter of the foramen magnum (labeled BC), the length of the clivus (labeled AB), and the length of the posterior occipital (labeled CD) in the HFS group were all reduced, and the differences were statistically significant. BE is positively correlated with AB and CD, with a stronger correlation observed between BE and AB (r = 0.487, p < 0.01). AB is negatively correlated with AD (r = −0.473, p < 0.01). The remaining correlations between the data were not statistically significant. There was no overlap in the 95% confidence interval for any of the measurements between the hemifacial spasm group and the control group. Conclusion There is a correlation between the posterior cranial fossa and hemifacial spasm.